PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO AND FOUR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 27 PADANG - Korza Putri, Utami; Delsi K, Delsi K; febriana, Rina (STKIP PGRI Sumbar, 2014)
Abstract This research is motivated by the students mathematical concepts understanding are still low. This research is head for determine whethert students mathematical concepts understanding by using active learning The Power of Two and Four Type is better than students mathematical concepts understanding taught by conventional learning. Type of this reaserch is experimental reaserch, with the Random Research design toward the subject. The population of this research is VIII class students of the SMPN 27 Padang in lessons 2013/2014. Technique of the sampling is the random ways, and the selected as the sample class is VIII.6 as experimental class and VIII.4 as control class. Instrument used in this reaserch is the last test of the matematic concept understanding. The test form used is essay form with reliabilities test is ,88. The data analysis technique used is the one side test with the help of MINITAB software, hypothesis test results P-value=0,004 is less than α=0,05, so the hypothesis of this research is accepted and with the resault can be inferred that students matematic concept understanding by applying the active learning the power of two and four type is better than student matematic concept understanding taught by conventional learning the VIII class students of the SMPN 27 Padang.